A Voltammetric Study on the Aqueous Electrochemistry of Acid Red 1 (Azophloxine) - Bicer, E.; Arat, C. (Croatian Chemical Soc, 2009)
Aqueous electrochemistry of Acid Red 1 (AR 1) was studied using cyclic voltammetry and square-wave voltammetry in Britton-Robinson buffers (pH = 2-12). The recorded cyclic voltamograms of AR 1 displayed one-irreversible peak which was attributed to reduction of the azo group in the entire pH values. However, two adsorption peaks on the square-wave voltamograms were also seen except for the reduction peak of azo group in the AR 1 molecule. In the pH range from 3.0 to 11.5, the first adsorption peak was observed at more positive potential from that of the azo group, and its potential depended on the pH of electrolyte solution. As the contrary to the first adsorption peak, the second one at more negative potential from that of the azo group was observed over the pH range from 2.0 to 6.5, and its potential was not practically dependent on the pH. According to the obtained voltammetric data, a plausible mechanism for the reduction of AR 1 was suggested. Moreover, the adsorption of AR 1 at the mercury-electrolyte interface was also investigated at different pH values. The peak current variations with the deposition time and AR 1 concentration were present. The Henry isotherm was employed for adjusting the experimental results at pH = 4.0 while the Langmuir isotherm was used for the data at pH = 7.0 and 10.0, and the values of the Gibbs free energy of adsorption were calculated. Nevertheless, the adsorption isotherm at pH = 10.0 showed that small repulsive interactions between the adsorbed AR 1 molecules on mercury electrode were present at longer deposition times. The pH of the supporting electrolyte played an important role on the adsorption behaviour of AR 1.
Keywords: Acid Red 1; Adsorption; Cyclic and Square-Wave Voltammetry; Mechanism